A Neuroadaptive Cognitive Model for Dealing With Uncertainty in Tracing Pilots' Cognitive State. (14th July 2020) - Klaproth, Oliver W.; Halbrügge, Marc; Krol, Laurens R.; Vernaleken, Christoph; Zander, Thorsten O.; Russwinkel, Nele
Abstract: A model‐based approach for cognitive assistance is proposed to keep track of pilots' changing demands in dynamic situations. Based on model‐tracing with flight deck interactions and EEG recordings, the model is able to represent individual pilots' behavior in response to flight deck alerts. As a first application of the concept, an ACT‐R cognitive model is created using data from an empirical flight simulator study on neurophysiological signals of missed acoustic alerts. Results show that uncertainty of individual behavior representation can be significantly reduced by combining cognitive modeling with EEG data. Implications for cognitive assistance in aviation are discussed. Abstract : When people are performing a task, it is hard to know whether they are about to make a mistake. Klaproth, Halbrügge, Krol, Vernaleken, Zander, and Russwinkel address this by recording EEG signals while people are performing a flight control task, and show that by examining the EEG signal they can determine when people failed to notice particular stimuli, which could lead to better assistive tools.